Spatial Distribution of Phytoplankton Community Composition and Their Correlations with Environmental Drivers in Taiwan Strait of Southeast China - Yong Zhang; Jin-Zhu Su; Yu-Ping Su; Hong Lin; Yang-Chun Xu; Balaji P. Barathan; Wan-Ning Zheng; Kai G. Schulz (Diversity, 2020)
Large-scale dinoflagellate blooms have appeared in recent decades in the Taiwan Strait, Southeast China. To study spatial variability of phytoplankton community composition, physical and chemical environmental drivers in surface seawater of the Taiwan Strait, we conducted cruises in May and July 2019. Cell numbers of dinoflagellates were significantly higher than that of diatoms in most sampling stations during the cruise in May, whereas diatoms were the major contributor to autotrophic biomass in July. Phytoplankton community shifted from a dinoflagellate- and diatom-dominated system in May to diatom dominance in July. The dominant phytoplankton species (genera) were the harmful algal bloom dinoflagellates Prorocentrum donghaiense and Scrippsiella trochoidea and the diatoms Coscinodiscus in May, and Rhizosolenia, Pseudo-nitzschia, and Guinardia in July. Cell densities of dinoflagellates and P. donghaiense reduced exponentially with increasing seawater temperature and salinity and decreasing dissolved inorganic nitrogen (DIN) concentrations. Based on the results of our work and previous studies, it becomes obvious that harmful dinoflagellate blooms are likely to be a major component of the planktonic food web in the Taiwan Strait at a temperature of 17.0–23.0 °C, a salinity of 29.0–33.0 psu, and a DIN concentration higher than 2.0 μmol L–1.